Legal Liability for Doctors' Malpractice Through Liability Insurance - Lavenia, Mela; Khoironi, Moh.Luay; Widiastuti, Widiastuti; Ngura, Serlin Peda (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study discusses the problems faced by doctors in Indonesia regarding their responsibility towards patients as third parties for their negligence resulting in medical malpractice against patients that is believed to have caused harm to the patient. Through a regulatory approach, this study analyzes the legal framework that regulates the urgency of doctors to obtain professional liability insurance, the requirements that must be met by doctors to file liability insurance claims, and the obstacles that doctors often face when applying for liability insurance. By considering different legal perspectives, this study aims to provide a deeper understanding of the legal solutions faced by doctors when committing medical malpractice or medical disputes.